Does local business ownership insulate cities from economic shocks? - Jed Kolko; David Neumark (Institute for the Study of Labor (IZA), 2009)
We assess a prominent argument for local economic policies that favor locally-owned businesses - namely, that locally-owned firms are more likely to internalize the costs to the community of decisions to reduce employment and hence help to insulate cities from adverse economic shocks. We test this argument by examining how establishment-level employment responses to economic shocks are affected by establishment ownership. We find evidence hat some types of local ownership do insulate regions from economic shocks, although the clearest benefits do not come from small, independent businesses, but instead from corporate headquarters and, to a lesser extent, from small, locally-owned chains.
urn:nbn:de:101:1-200910122565
Keywords: R11; R38; J23; 330; Local ownership; employment shocks; employment stability; Kommunale Wirtschaftsentwicklung; Eigentümerstruktur; Schock; Unternehmensentwicklung; Arbeitsplatzsicherung; Beschäftigungseffekt; USA